PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENUMBUHKEMBANGKAN HIGHER ORDER THINKING SKILL SISWA SEKOLAH DASAR - Cholifah Tur Rosidah (Universitas PGRI Adi Buana Surabaya, 2018)
Study about implementation of Problem Based Learning (PBL) model to develop Higher Order Thinking Skill (HOTS) in elementary school’s student. This article was written through study literature. Problem Based Learning is a model with teaching approach at authentic issue, so the students are able to compose their knowledge own. Characterized of Problem Based Learning is using the real life problem as something to be learned students to train and improved the skills of think critically and problem solving in order to obtain concepts knowledge. HOTS or the capacity to think a high degree is one of components must be maintained in any process learning did as teachers on the application of 2013 Curriculum. Learning activities must be designed that students have skills think high level. Through a Problem Based Learning model, higher order thinking skill of students will be trained and developing, and they can gain experience directly and change mannerisms (knowledge, skills, attitude) both in terms of quality and quantity